If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -8x = 89 + -29x Solving 14 + -8x = 89 + -29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29x' to each side of the equation. 14 + -8x + 29x = 89 + -29x + 29x Combine like terms: -8x + 29x = 21x 14 + 21x = 89 + -29x + 29x Combine like terms: -29x + 29x = 0 14 + 21x = 89 + 0 14 + 21x = 89 Add '-14' to each side of the equation. 14 + -14 + 21x = 89 + -14 Combine like terms: 14 + -14 = 0 0 + 21x = 89 + -14 21x = 89 + -14 Combine like terms: 89 + -14 = 75 21x = 75 Divide each side by '21'. x = 3.571428571 Simplifying x = 3.571428571
| -6x+6(-2x-12)=144 | | 2a^2+18a+28= | | 9x(2x+7)= | | 2345x-678=678 | | 5(3-2x)=75 | | 2x^2+13x=24 | | -496=-8(-10x-8) | | -165=5(5x-3) | | 5x+1=7+3x | | 160=-7x-6(2x+5) | | 4(5x+7)+-8=-16 | | 3(x-1)=3x+2 | | 8x+8=8x+12 | | 4r+15=4r+11 | | 4xy*6xy= | | -2(4x+5)-11=-5 | | 2x-2=x+x | | 23x-8-14x=10 | | 2(b+8)-9=9 | | 2x^2=-144 | | 3k^2-11k-20=0 | | (8x^3)(2)= | | -8b+9+6b=3b+14 | | (4xy)(6xy)= | | 1+7=43+x | | 234x-67=56 | | y-2=y+3 | | 4(5x-7)-8x=-5 | | 4xy+6xy= | | 6x+24=12x+14 | | 6x-(4x+7)= | | 5a+4(2a+4)= |